Efektivitas Layanan Informasi Dengan Menggunakan Video Animasi Untuk Mereduksi Cabin Fever Pada Mahasiswa Bimbingan dan Konseling Universitas Adi Buana Surabaya - Nisa, Anaa Farihatun; Lathifah, Maghfirotul (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2022)
This research is motivated by a phenomenon that is currently happening, namely the COVID-19 pandemic which requires quarantine and self-isolation so that it affects a person being exposed to cabin fever. Cabin fever is an emotion or sad feeling that arises as a result of prolonged isolation in the home or certain places. The method used was quantitative with the pre-experimental research design. The design form used was the pretest-posttest one-group design. Data analysis using non-parametric statistics, namely Wilcoxon Signed Ranks Test by SPSS for windows version 24.0. The results of this study can be concluded that there was an increase before receiving treatment that is 40 while after receiving treatment decreased to 29. Thus, there was a decrease of 27.5% so it can be concluded that the guidance of the effective group to reduce cabin fever in students’ guidance and counseling class 2017 Adi Buana University.